PENGARUH MODAL KERJA TERHADAP LABA BERSIH PADA PT POS INDONESIA (PERSERO) MPC BANDUNG PERIODE 2012-2016 - HANI HATIMATUNNISANI; WILDAN NISPIANI (EKBIS (Ekonomi & Bisnis), 2018)
This study aimed to know the influence of working capital to net income at PT. Pos Indonesia (Persero) Mail Processing Centre Bandung. The research used quantitative methods. The data collection techniques used literature research and documents. The result showed that the testing on the influence of working capital to net income is working capital had very influence to the net income, in which working capital gived influence 90,9% to net income at PT. Pos Indonesia (Persero) Mail Processing Centre Bandung and the rest about 9,1% was influence by other variables. The problems faced by PT. Pos Indonesia (Persero) are 1). The growth of revenue is less significant. 2). The company difficulty to increase service capacity. 3). Was decrease of current asset.